Metode Live Memory Acquisition untuk Pencarian Artefak Digital Perangkat Memori Laptop Berdasarkan Simulasi Kasus Kejahatan Siber - M. Ainul Yaqin; Triawan Adi Cahyanto; Nur Qadariyah Fitriyah (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2021)
Information technology's hardware and software are constantly evolving. The rise in cybercrime cases is consistent with this trend. While operating systems can be hacked, personal data can be stolen and encrypted, making it impossible for users to access the information. Cybercriminals are using social media data to target personal information currently. Users' usernames, passwords, and other personal information can be stored in a device's memory, as well as browser cookies. Pre-analysis, analysis, and post-analysis are the three stages of the research process. "Live Memory Acquisition" is the proper method for obtaining data from a device's memory. There is digital evidence in the form of an email address, a password, Facebook, and PayPal accounts as well as a link URL discovered in the analysis of the results of the acquisition of artifact one. The results of the artifact 2 acquisition did not reveal any passwords. There was no evidence of email or Facebook passwords in the analysis of artifact 3 acquisition results, but the overall data test results showed that the total number of test results on artifact 1 was 100%, 57.14% on artifact 2, and 71.42% on artifact 3.